Porcine embryo collection using single subcutaneous administration of follicle-stimulating hormone in a large volume of saline - Kenzo UCHIKURA; Rumiko YAMAMOTO; Shigeyuki TAJIMA; Masahiro SUZUKI; Ayumi SAGARA; Takayuki KURITA (The Society for Reproduction and Development, 2020)
The effects of a single subcutaneous or intramuscular injection of follicle-stimulating hormone (FSH) on follicular growth and expression of estrous behavior and its single subcutaneous administration on the number of corpora lutea (CL) and embryos were investigated in pigs. All four sows that were subcutaneously administered 5 AU FSH expressed normal estrus and had no ovarian cysts. Two of the four sows that were administered 5 AU FSH intramuscularly did not exhibit estrus, and another sow had a short estrus period. All four sows had ovarian cysts. The mean numbers of CL, embryos, and blastocysts following the subcutaneous administration of 5 AU FSH (16.8, 16.0, and 13.8, respectively) did not differ significantly from those for the control animals treated intramuscularly with 1000 IU equine chorionic gonadotropin (18.5, 16.5, and 14.3, respectively). In conclusion, embryo recovery was possible using a single subcutaneous administration of FSH.